Tonal disruption in the speech of a language-delayed thai adult - Jack Gandour (2018)
An acoustic-perceptual investigation was performed on fundamental frequency (F 0 ) contours associated with lexical tones in the speech of one 21-year-old adult speaker of Thai who did not start speaking until age 7. Thai is a tone language with five lexically contrastive tones-mid, low, falling, high, and rising. Measures of F, were taken from a minimal set of five monosyllabic citation forms. Results from phonemic identification tests indicated that AY exhibited a selective disruption in the production of Thai tones. In contrast to the normal Thai tone space, AY's tone space was reduced to three tones-mid, low, and rising. Acoustic analysis revealed that AYï? 1/2 s aberrant F 0 contours for the falling and high tones were virtually identical in terms of height and overall shape; both exhibited a slow, steady fall in F 0 in the upper range of AY's tone space. Listeners' failure to perceive AY's intended productions of the falling and high tones confirmed the perceptual importance of rapid change in F 0 slope in the Thai tone space. Findings are discussed with reference to the chronological order in which Thai tones are acquired in normal language development. © 1989 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.